Principios de odontogeriatría - Reyes, Carlos Alfonso (Revista Estomatología, 1992)
The old people’s oral health, not only has to do with an Stomatognatich system or with the necessity of a dental prothesis. It’s needed to study the old people as a whole developing knowledge about elderly, aging and old age. It has to be taken into a count that old people as patiens have different and special characteristics compared with those of children and adults. For this reason it"s essential to defferentiate between phisiological changes that can appear in old people, in his organs and systems, including the stomatognathic system, why the Geriatic Dentistry has become a new speciality in dentistry.